The Relationship Between Environmental Physical Conditions and the Incidence of Malaria in Percut Sei Area, Chart XV Percut Village - Meutia Nanda; Anissa Humaira; Meida Sari Siregar; Tania Yusrina; Ismi Larasati Hasibuan (Universitas Muhammadiyah Palu, 2024)
Environmental factors have an important role in the incidence of Malaria. The environment provides physical conditions that allow the Malaria disease vector, Anopheles Sp., to multiply. Anopheles Sp. has the ability to adapt to its surroundings, allowing it to survive. The purpose of this study is to determine the relationship between environmental conditions and the incidence of malaria in the Percut Sei area, Bagan XV, Percut Village. This study uses a quantitative method with an approach using a cross sectional design. The population in this study was 300 people using the lameshow formula, 51 samples were obtained in the study with random sampling techniques, The results of the study on the type of wall had a significant relationship with the incidence of malaria with a Pvalue of 0.006 < 0.05. In the presence of gauze wire there is a significant relationship with the incidence of malaria with a Pvalue value of 0.000 < 0.05. In waterlogging, there was a significant relationship with the incidence of malaria with a Pvalue value of 0.028 < 0.05. In the existence of livestock cages, there was a significant relationship with the incidence of malaria, the Pvalue value obtained was 0.024 < 0.05. In the activity of going out at night, a significant relationship was obtained with a Pvalue value of 0.000 < 0.05. From this study, it is hoped that community members will maintain environmental conditions to avoid malaria attacks caused by the Anopheles mosquito.Sp.